Common and much less common scenarios in which botany is crucial for forensic pathologist and anthropologists: a series of eight case studies - Caccianiga, Marco; Caccia, Giulia; Mazzarelli, Debora; Salsarola, Dominic; Poppa, Pasquale; Gaudio, Daniel; Cappella, Annalisa; Franceschetti, Lorenzo; Tambuzzi, Stefano; Maggioni, Lidia; Cattaneo, Cristina (International journal of legal medicine, 2021)
It is commonly accepted that crime scene recovery and recording are key moments of any judicial inspection in which investigators must decide on the correct strategies to put into place. Complex outdoor scenarios, presenting partially or entirely skeletonised remains, can benefit more than others by the intervention of environmental specialists (forensic anthropologists, archaeologists, entomologists and botanists). These experts are capable of singling out, correctly recording and recovering environmental evidence that can lead to a more comprehensive reconstruction of a given criminal episode. If human remains are discovered in an outdoor scenario, the on-site presence of a botanist will guarantee a correct approach to the identification, recording and recovery of any botanical evidence. If an on-site botanist is not available, the operators must be capable of both the botanical evaluation of a scene and the implementation of correct botanical sampling protocols.The following collection of unusual case histories that aim at underlining the efficacy of forensic botany will examine the determination of post mortem or the post depositional interval, evidence for a victim's post mortem transfer, evidence for the identification of a primary crime scene and evidence for the identification of a victim's dismemberment site. In another two cases, one, we will illustrate the important role that forensic botany played in the discrimination between botanical material used to voluntarily conceal a victim and vegetation that had grown naturally above a disposal site, whereas the other will highlight the protocols implemented for the identification of a murder weapon.
Keywords: Female; Forensic botany; ženské pohlaví; Forensic Sciences; Body Remains; PMI; lidé; Skeletonised human remains; soudní vědy; botanika; Male; Botany; smrt; Murder weapon; Concealment locations; mužské pohlaví; Death; Crime Victims; oběti zločinu; Dendrochronology; tělesné pozůstatky; Humans